The common noctule bat (Nyctalus noctula): population trends from artificial roosts and the effect of biotic and abiotic parameters on the probability of occupation. Issue 1 (11th December 2021) - Printz, Lisa; Tschapka, Marco; Vogeler, Anna
Abstract: As urbanization and intense forestry management are increasing, natural bat roosting opportunities, e.g. tree cavities, are constantly declining. A common management practice, especially in urban environments, is the installation of bat boxes. We assessed (1) abundance trends inside artificial bat boxes of the noctule bat ( Nyctalus noctula ) over 11 years in Neu-Ulm, Germany, and identified (2) parameters affecting the occupation rate. Further, we compared (3) abundance of noctule bats in bat boxes between areas with large availability of natural roosts (forests) and urban areas with primarily artificial roosting structures (parks). Our results revealed a severe decline of noctule bats over 11 years. Further, our results indicate that bat boxes cannot fully replace natural tree cavities. Nonetheless, they support roost availability in areas already altered and providing only low amounts of natural bat roosts. The findings of our study have important implications for the conservation of bats in urbanized landscapes and underline the importance of old and intact forests for local biodiversity.